Islamic Education Reconstruction: Mastery Learning Based in Modern Islamic Boarding School - Lila Pangestu Hadiningrum (State Institute of Islamic Studies (IAIN) Palu, 2017)
The growing secularism and radicalism are increasingly widespread in Islamic education system. Efforts to reconstruct the Islamic educational system have been done but results yet to satisfy Muslim society. Comprehensive teaching in Islamic boarding school is expected to be a solution to solve problems relating to moral, role mode, and leadership crisis as well as the commercialization of education. The implementation of mastery learning in modern Islamic boarding school is considered as a breakthrough in improving and implementation of integrated learning and curriculum. Islamic boarding school is expected to become one of role model in Muslim education institutions which is able to produce high quality of human resources with high work ethic and morale.